Observation of Unconventional Charge Density Wave without Acoustic Phonon Anomaly in Kagome Superconductors AV_{3}Sb_{5} (A=Rb, Cs) - Haoxiang Li (American Physical Society, 2021)
The combination of nontrivial band topology and symmetry-breaking phases gives rise to novel quantum states and phenomena such as topological superconductivity, quantum anomalous Hall effect, and axion electrodynamics. Evidence of intertwined charge density wave (CDW) and superconducting order parameters has recently been observed in a novel kagome material AV_{3}Sb_{5} (A=K, Rb, Cs) that features a Z_{2} topological invariant in the electronic structure. However, the origin of the CDW and its intricate interplay with the topological state has yet to be determined. Here, using hard-x-ray scattering, we demonstrate a three-dimensional CDW with 2×2×2 superstructure in (Rb,Cs)V_{3}Sb_{5}. Unexpectedly, we find that the CDW fails to induce acoustic phonon anomalies at the CDW wave vector but yields a novel Raman mode that quickly damps into a broad continuum below the CDW transition temperature. Our observations exclude strong electron-phonon-coupling-driven CDW in AV_{3}Sb_{5} and support an unconventional CDW that was proposed in the kagome lattice at van Hove filling.